Online awareness is associated with superior performance on assessments of functional cognition - Marks, Timothy S.; Giles, Gordon Muir; Edwards, Dorothy Farrar (Frontiers in Aging Neuroscience, 2024)
Background Intact awareness facilitates an individual’s adoption of strategies to support community living skills. However, most studies have not examined awareness during ongoing complex task performance. Objective: To examine whether community-dwelling adult’s Accuracy and Strategy use on the Weekly Calendar Planning Activity 17-item version (WCPA-17), Total Cues on the Performance Assessment of Self-care Skills Checkbook Balancing and Shopping Task (PCST), and scores on the self-report Alzheimer’s Disease Cooperative Study – Activities of Daily Living Scale (ADCS-ADL) differ between groups who do and do not demonstrate awareness of performance difficulties on the WCPA-17. Methods Using data collected as part of a larger study we performed a cross-sectional analysis of 274 community-dwelling adults aged 55 to 93 years. Two methods classified participants into groups aware or unaware of their performance. Independent sample t-tests examined group differences on four dependent variables: Accuracy and Strategy use on the WCPA-17, PCST Total Cues, and score on the ADCS-ADL. Results Using one classification method, aware individuals showed superior Accuracy (p < 0.001), used more Strategies (p = 0.002), needed fewer PCST Total Cues (p < 0.001), and reported greater independence on the ADCS-ADL (p < 0.004), similar trends were observed with the other method in Accuracy (p < 0.001) and PCST Total Cues (p < 0.001) but Strategy use and ADCS-ADL differences failed to reach significance after Bonferroni correction. Conclusion Groups categorized as aware performed better on all measures. Intact awareness is critical to performance on complex everyday activities and can be evaluated with functional cognition assessments.